If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -1(5c + -6) = 1 Reorder the terms: 6x + -1(-6 + 5c) = 1 6x + (-6 * -1 + 5c * -1) = 1 6x + (6 + -5c) = 1 Reorder the terms: 6 + -5c + 6x = 1 Solving 6 + -5c + 6x = 1 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -5c + -6 + 6x = 1 + -6 Reorder the terms: 6 + -6 + -5c + 6x = 1 + -6 Combine like terms: 6 + -6 = 0 0 + -5c + 6x = 1 + -6 -5c + 6x = 1 + -6 Combine like terms: 1 + -6 = -5 -5c + 6x = -5 Add '-6x' to each side of the equation. -5c + 6x + -6x = -5 + -6x Combine like terms: 6x + -6x = 0 -5c + 0 = -5 + -6x -5c = -5 + -6x Divide each side by '-5'. c = 1 + 1.2x Simplifying c = 1 + 1.2x
| m^3-m^2-4m-4=0 | | -7-48=m | | -9=0(0)+b | | 11/3/21/2=x/5 | | -4-(-7)=m | | -1-(-2)=m | | 2/9=x/40 | | -7-30=m | | 1/3=x/25 | | 6/10=20/x | | 4=-9(0)+b | | -13x=39x^2 | | -4(5y-7)+2(4y+6)=m | | -4*5=m | | 7/9=5/x | | 1/6=x/48 | | 7/x=35/50 | | 2x/3+19/9=x/6 | | k+5k= | | k*5k= | | 3x+0=2 | | 5/8=x/24 | | ((b^2)/(-2a^4))^3 | | -9-(-8)=m | | 3x+14=0520 | | 2-3-2+3=m | | 5y-3y-7y+7y=m | | 0-8=m | | -20-(-14)=m | | -19-(-18)=m | | -119-7=8x+16 | | 16t^2=1085 |